2020
DOI: 10.1002/pat.5046
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of flame retardancy in bio‐resourced mannitol based curing agent for clear pressure‐sensitive adhesive

Abstract: Highlights • Research involves the preparation of phosphorus modified curing agents of biobased resources and understand in the application in the clear pressure-sensitive adhesive. • A bio-based curing agent has synergic behavior of flame retardancy. • The use of a bio-based curing agent imparts thermal stability in the adhesive. • The presence of phosphorus in the structure allows the formation of intumescent char.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 65 publications
(87 reference statements)
0
3
0
Order By: Relevance
“…Thermal crosslinking of pressure-sensitive adhesives consists of the formation of intramolecular bonds in the polymer chain and between them, leading to the formation of intramolecular networks in the composition, by reaction of end groups (functional groups) of the selected crosslinking compound (or compounds) with the functional groups or unsaturated bonds of the polymer used as pressure-sensitive adhesive, under the influence of high temperature through crosslinking by a radical mechanism that is initiated at high temperature [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…Thermal crosslinking of pressure-sensitive adhesives consists of the formation of intramolecular bonds in the polymer chain and between them, leading to the formation of intramolecular networks in the composition, by reaction of end groups (functional groups) of the selected crosslinking compound (or compounds) with the functional groups or unsaturated bonds of the polymer used as pressure-sensitive adhesive, under the influence of high temperature through crosslinking by a radical mechanism that is initiated at high temperature [6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…A suitable kind of crosslinkers has been commonly adopted to solve the above problems. 7,14 However, some studies demonstrated that the introduction of crosslinkers might improve the shear strength at the expense of the peel strength. [15][16][17] Wang et al 18 obtained flame-retarded biobased PSAs containing multifunctional epoxidized soybean oils (ESO) as crosslinker.…”
Section: Introductionmentioning
confidence: 99%
“…The high loading of DMMP required to achieve flame retardancy inevitably deteriorates these properties due to the plasticization effects. A suitable kind of crosslinkers has been commonly adopted to solve the above problems 7,14 . However, some studies demonstrated that the introduction of crosslinkers might improve the shear strength at the expense of the peel strength 15–17 .…”
Section: Introductionmentioning
confidence: 99%